Competences of polish nurses in the field of prescribing medications: A systematic review - Kasperska-DÄ™bowska, Paulina; Oleksy, Eliza; Wojtczak, Anna; Wojtysiak, Katarzyna; Dreliszak, Jakub; Wielgus, Adriana (Humanities & Social Sciences Reviews, 2021)
Purpose: The purpose of the following systematic review is to present polish regulations in terms of education, acquiring competencies in the field of prescribing drugs and medical devices. Methodology: The following review can be helpful to conduct comparative meta-analyses. Internet System of Legal Acts, PubMed, Google Scholar research was used to analyze the topic. The selected keywords were used to find information sources: law, competence, nurse, prescribing, medication, medical devices. Articles were selected according to regulations in Poland in terms of education, acquiring competencies in the field of prescribing drugs and medical devices. Main findings: The increase in nurses' competencies is equivalent to a greater need for knowledge and new knowledge acquired. Nurses take part not only in care and treatment, but also takes independent actions. In such enormous responsibilities, it is crucial to focus on the development of skills. Thus, a competent nurse is interested in continuous professional and personal growth and provides patients with high-quality nursing trustees. Implications of this study: The results should be considered in health care units, especially Primary Healthcare Units. The paper indicates the regulations in terms of education, acquiring competencies in the field of prescribing drugs which should be revised by personnel and implemented to improve the work of the healthcare unit. Novelty in this study: There is a lack of systematic reviews of the regulations in Poland in terms of education, acquiring competencies in the field of prescribing drugs and medical devices. The paper is an attempt to assess the topic.